PENGARUH LATIHAN CIRCUIT PLYOMETRIC TERHADAP FREKUENSI TENDANGAN SPEED KICK AP CHAGI PADA ATLET TAEKWONDO STAR FIGHTER ACADEMY - Aji, Umbo; Hidayah, Taufiq (Universitas Muhammadiyah Cirebon, 2025)
This study aims to examine the effect of Circuit Plyometric training on improving the Ap Chagi kick frequency among beginner athletes at the Star Fighter Taekwondo Academy. The main issue addressed in this research is the low speed and number of kicks performed by novice athletes during matches, which affects the effectiveness of attacks and the chances of scoring points. The research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The subjects consisted of 23 beginner athletes aged 8 to 14 years, selected through purposive sampling. The Circuit Plyometric training program was conducted over six weeks, with a total of 18 sessions (three times per week). Data were collected through an Ap Chagi kick frequency test conducted over a 10-second period before and after the intervention. The results showed an increase in the average kick frequency from 17.35 (pretest) to 21.00 (posttest). The N-Gain score of 0.318 was categorized as moderate based on Hake’s (1998) classification, indicating that the training was reasonably effective in enhancing kick frequency. This effectiveness is associated with the characteristics of Circuit Plyometric training, which involve explosive movements that stimulate leg muscle strength and speed. This research contributes as a scientific reference for coaches and athletes in designing more specific, measurable, and applicable physical training programs. This method is recommended to support the improvement of basic kicking techniques in beginner taekwondo practitioners, both in regular training and in preparation for competition.